Impacts of human activities on nutrient transport in the Yellow River: The role of the Water-Sediment Regulation Scheme - Li, Xinyu; Chen, Hontao; Jiang, Xueyan; Yu, Zhigang; Yao, Qingzhen (The Science of the total environment, 2017)
Anthropogenic activities alter the natural states of large rivers and their surrounding environment. The Yellow River is a well-studied case of a large river with heavy human control. An artificial managed water and sediment release system, known as the Water-Sediment Regulation Scheme (WSRS), has been carried out annually in the Yellow River since 2002. Nutrient concentrations and composition display significant time and space variations during the WSRS period. To figure out the anthropogenic impact of nutrient changes and transport in the Yellow River, biogeochemical observations were carried out in both middle reaches and lower reaches of the Yellow River during 2014 WSRS period. WSRS has a direct impact on water oxidation-reduction environment in the middle reaches; concentrations of nitrite (NO2−) and ammonium (NH4+) increased, while nitrate (NO3−) concentration decreased by enhanced denitrification. WSRS changed transport of water and sediment; dissolved silicate (DSi) in the middle reaches was directly controlled by sediments release during the WSRS while in the lower reaches, DSi changed with both sediments and water released from middle reaches. During the WSRS, the differences of nutrient fluxes and concentrations between lower reaches and middle reaches were significant; dissolved inorganic phosphorous (DIP) and dissolved inorganic nitrogen (DIN) were higher in low reaches because of anthropogenic inputs. Human intervention, especially WSRS, can apparently change the natural states of both the mainstream and estuarine environments of the Yellow River within a short time. [Display omitted] •Daily variations of nutrients during WSR period in the Yellow River•Nutrient changes during water–sediment regulation event.•The effects of Yellow River sediment–water regulation event on the nutrients' speciation and concentration.•Sources of nutrients in the downstream of the Yellow River